Cooperation between Vocational Training institutions and companies: an initiative from the Telefónica Foundation and the Society of Jesus in Spain (Journal of Parents and Teachers, 2014)
On 18 July, the Executive Vice President of Fundación Telefónica, Emilio Gilolmo and the Provincial of the Jesuits in Spain, José Francisco Ruiz SJ, signed a cooperation agreement that wil provide a new system of training grants for students who will start their vocational training studies during the next academic year 2014-15.This agreement involves financing from Fundación Telefónica of a Study Grants Program which aims to help and promote access and continuity in the training of socioeconomically disadvantaged young people. With the support of Fundación Telefónica, Jesuit schools will offer several kinds of grants to their students covering the actual costs of education and providing equal opportunities based on the individualized needs of each student.
Keywords: Fundación Telefónica; Training; Society of Jesus; Education; Experiences